PENGARUH MODEL THINK PAIR SHARE (TPS) TERHADAP HASIL BELAJAR SISWA PADA MUATAN PELAJARAN PPKN KELAS V SDN 09 AMPENAN - Muhammad Alwan; Heri Hadi Saputra; Ilham Syahrul Jiwandono (JURNAL ILMIAH PENDAS: PRIMARY EDUCATION JOURNAL, 2021)
This study aims to determine the effect of the Think Pair Share (TPS) Model on student learning outcomes in class V civics subject content of SDN 09 Ampenan. This study uses the Ex Post Facto research method. The preparation of this thesis was carried out from June to July 2020. The population in this study consisted of 94 students. The sampling technique used was purposive sampling with 32 students in class V.A. The data collection technique uses a survey method through questionnaire data collection method that has been carried out by expert testing and documentation. The data analysis method used hypothesis testing using the t test with the assistance of SPSS 201 for Window. With the prerequisite test for normality and homogeneity of data. The results of the analysis show that the learning implementation questionnaire data is categorized as good according to the score obtained, which is 80. For data on student learning outcomes it is said to be normal with the results of the analysis of .194 for the initial value (application of the conventional model) meanwhile for the application of the TPS model the significant value is 356. If interpreted, the value becomes 0.194 for the conventional model and 0.356 for the application of the Think Pair Share model. When compared with a significant level of 0.05. The significant value of the normality test of the two values ​​is greater than 0.05, which means that the data for the two values ​​can be said to be normally distributed. Furthermore, for the homogeneity test, the results obtained a significance value of 0.110> 0.05, so the data is normally distributed and homogeneous. Hypothesis testing with t test obtained a significance value of 0.000 <0.05 so that H0 is rejected and Ha is accepted. The results of the analysis show that there is an effect of the Think Pair Share (TPS) Model on student learning outcomes in in class V civics subject content of SDN 09 Ampenan